The effect of neck collars on the behaviour, weight and breeding success of Mute Swans Cygnus olor - Spray, C J; Bayes, K (Wildfowl, 1992)
Neck collars were used as an individual marking technique in a population study of wild Mute Swans on South Uist, Scotland from 1978-82. This was the first time this method of marking birds had been extensively used in Britain, and data were collected on the effect of the collars on behavior, weight and breeding success. Collars made of laminated plastic were fitted to over 650 swans during the moult and brood catches. Behavioral observations were undertaken in July and November 1980 at two sites used by flocks of swans. Collars did not affect the frequency of feeding, but there was a significant difference in the type of feeding method employed. Collared birds upended less often than uncollared birds at both sites. The weights of collared birds however were not different, and neither was their breeding success. No chewing or scarring was recorded on the collars and no damage to neck feathers of marked birds. The frequency of preening showed no consistent pattern between collared and uncollared birds and neither did the area being preened. Implications of these results are discussed in relation to the main advantages of using collars as a marking technique in other studies, and possible drawbacks.